2016
DOI: 10.5466/ijoms.14.67
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Mild Hypoxia Associated with Oral Breathing Affects The NK Cell Ratio in The Spleen

Abstract: An upper respiratory tract obstruction due to nasopharyngeal diseases such as allergic rhinitis and tonsillar hypertrophy/sinusitis in growing children inhibits normal nasal breathing and leads to oral breathing. One symptom of this phenomenon appearing in the living body is hypoxia. Typically, it is rare for hypoxia associated with an upper respiratory obstruction to become severe and cause dyspnea, and it generally causes mild hypoxia.However, there are no previous reports regarding the effect of mild hypoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Therefore, we blocked the nose unilaterally in rats. Such a model for unilateral nasal obstruction in rats has been published earlier . Mouth breathing due to nasal obstruction in humans reduces SpO 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we blocked the nose unilaterally in rats. Such a model for unilateral nasal obstruction in rats has been published earlier . Mouth breathing due to nasal obstruction in humans reduces SpO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study that aimed to examine the effect of mild hypoxia on the entire body, the changes in the immune system of growing rats using a mild hypoxia‐exposed model were evaluated. In that study, the exposure to mild hypoxia in growing rats was suggested to induce a persistent reduction in SpO 2 and changes in the natural killer cell ratio in splenic lymphocytes . However, the changes caused by long‐term nasal obstruction have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are in agreement with a hypoxia–ischemia model that showed that NK cells expression was reduced in the spleen [ 55 ]. However, another study showed that when rats were exposed to mild hypoxia, the NK cell ratio was significantly higher, but then decreased after 7 days [ 56 ]. Increasing evidence demonstrates that hypoxia regulates multiple immune processes, such as cell migration, antigen presentation and immune effector functions.…”
Section: Discussionmentioning
confidence: 99%